Green and Sturdy Lightweight Total Cement The Job of Waste and Reused Materials - VINOD, KUMAR G; SRAVAN, KUMAR ADIMALLA (The journal of contemporary issues in business and government, 2020)
“ Lightweight aggregate concrete manufactured from solid waste or recycled byproducts is a hot new issue in construction and building materials. Making Portland cement using this additive offers significant advantages in terms of lowering the impact on the environment and decreasing the amount of natural resources used in the production process.”This article discusses the use of agricultural and industrial wastes as cementitious materials or artificial lightweight aggregate concrete. Advanced microstructure characterization methods and mechanical properties were also examined. Future research will evaluate if it is possible to improve lightweight aggregate concrete manufactured from recovered solid waste and by- products in order to solve environmental issues or boost environmental advantages.